Assessing and predicting land cover dynamics for environmental sustainability in Jordan's arid ecosystems using CA-Markov model - Rana N. Jawarneh (18180424) (2024)
Jordan's arid ecosystems face a threat of environmental degradation due to increasing human activities driven by a growing population and economy. This study assesses Land Use and Land Cover (LULC) changes in regional and ecoregional landscapes, particularly in a region with an east-west environmental gradient, spanning 41 years (1990–2030). The study utilizes the Jordan National Land Cover Dataset (JNLCD) for historical data and employs the CA-Markov model to generate a future land cover map. The results revealsignificant changes, particularly the tripling in size of urban areas at the expense of primary croplands. The Steppe ecoregion, known for its fragility, experienced shifts into irrigated agriculture practices and loss of natural rangelands. The period between 2000 and 2015 marked as the most dynamic period as the region landscape underwent significant change due to population growth and influx of refugees. During this period, 123 km2 of rainfed agricultural areas were consumed by urbanization while rainfed agriculture activities expanded into sparsely-vegetated/barren areas (55 km2). Additionally, 33 km2 of sparsely-vegetated/barren areas were transformed into irrigated agriculture. This study offers a comprehensive and innovative analysis of LULC changes in Jordan's arid ecosystems. While it highlights the ecological importance of the region and its potential to enhance environmental resilience, it also underscores the negative impact of human interventions, which have disrupted spatial arrangement, connectivity, stability, and structure. By bridging historical data with future projections, employing detailed landscape metrics, and addressing socio-economic drivers, this work provides valuable insights for sustainable land use planning and environmental conservation in Jordan. Other Information Published in: Remote Sensing Applications: Society and Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rsase.2024.101262